(untitled) (Architecture Image Studies, 2025)
Freshwater scarcity remains a pressing global challenge, exacerbated by population growth, urbanization, and climate change. This study focuses on the design, development, and evaluation of a sustainable seawater desalination system that integrates ultrafiltration as a pre-treatment to reverse osmosis. The research include designing a compact and energy-efficient desalination system suitable for diverse environmental conditions, evaluating the effectiveness of ultrafiltration in reducing fouling and improving the lifespan of reverse osmosis membranes, and assessing the system’s ability to produce high-quality freshwater in compliance with the National Water Quality Standard (NWQS). The experimental results demonstrated significant improvements in water quality across key parameters. Salinity levels were reduced from 8.33 g/L in raw seawater to 0.27 g/L, while total dissolved solids (TDS) decreased from 7216 mg/L to 286 mg/L. Additionally, the system effectively stabilized the pH at 7.99, ensuring chemical safety and potable suitability. Ultrafiltration membranes proved highly effective in removing large particles, microorganisms, and organic contaminants, reducing fouling and enhancing the overall performance of reverse osmosis membranes. These findings underscore the importance of multi-stage filtration in achieving sustainable and efficient desalination. This research highlights the potential of integrating ultrafiltration and reverse osmosis technologies as a scalable and eco-friendly approach to addressing global freshwater scarcity.